Enhanced polyethylene terephthalate (PET) glycolysis with biochar-supported organic ionic liquid-based catalysts - Stuart Conroy; Fraser Norris; Elliot Ross; Stuart D. Robertson; Yong Xu; Ashleigh J. Fletcher; Xiaolei Zhang (Journal of Environmental Chemical Engineering, 2026)

Evaluating a structured expert elicitation approach for adaptive conservation management based on lessons from five years in practice - Helen J. Mayfield; James Brazill‐Boast; Mick Andren; Michiala Bowen; Adam Fawcett; Trent Forge; Luke Foster; Ross Goldingay; Paul Hillier; Meagan Hinds; Simon Lee; Erica Mahon; et al. (Conservation Biology, 2026)
Adaptive management of threatened species relies on having ex ante estimates of species’ responses to different interventions. Structured expert elicitation is often used to generate these estimates, but comparisons of these expert‐predicted outcomes with observed results are rare. This study aims to evaluate the utility of expert elicitation for adaptive management in the New South Wales Saving our Species program in Australia by revisiting six species management plans that were generated from tailored structured elicitation guidelines developed five years prior. Each species’ management plan included a defined scope, conceptual model, monitoring indicators, and estimated response to management curves under different scenarios. Experts reviewed the conceptual models after five years of management and compared the predicted response to management with observed monitoring data. In three of the six case studies, observed outcomes closely matched predictions. Where predictions diverged, factors such as unanticipated new threats and unexpected responses to interventions potentially contributed to discrepancies. However, in all cases, the structured approach provided a clear logic for planning, enabling managers to systematically refine their understanding. The conceptual models and response curves were valuable for collaborating, communicating, and generating hypotheses for unexpected results. This work demonstrates the value of tailored guidelines in supporting adaptive management processes and showcases the value of documenting expert knowledge in management settings with high uncertainty.

Morrittospora corbiculae n. gen. n. sp., a microsporidian parasite infecting the invasive Asian clam Corbicula fluminea from the River Thames, London - Rachel Foster; Kelly S. Bateman; Paul F. Clark; Matthew J. Green; Chantelle Hooper; Stuart H. Ross; Paul Stebbing; Georgia M. Ward; David Bass (Journal of Invertebrate Pathology, 2026)

The first report of Hematodinium perezi genotype I infection of Chinese mitten crab (Eriocheir sinensis) from the River Thames, UK - Rose C. Kerr; Hamish J. Small; David Bass; Wafa S. Al Arimi; Stuart Ross; Roland Pevsner; Bryony Williams; Ronny van Aerle; Grant Stentiford; Kelly Bateman (Journal of Invertebrate Pathology, 2025)

Comparative analysis of the temporal abundance of the epiphytic pest, Melanothamnus thailandicus, affecting farmed Kappaphycus striatus: Visual and molecular detection approaches - Joseph P. Faisan; Rema C. Sibonga; Maria Rovilla J. Luhan; Victor Marco Emmanuel N. Ferriols; Jonalyn P. Mateo; Janina Brakel; Juliet Brodie; Georgia M. Ward; David Bass; Stuart Ross; Grant D. Stentiford; Claire Gachon; et al. (Journal of Applied Phycology, 2025)

Is South Africa afflicted by the resource curse? - Ross Harvey; Stuart Morrison; Pranish Desai (The Extractive Industries and Society, 2025)

Identification of Albopleistophora grylli n. gen. n. sp. (Microsporidia) and its impact on crickets (Gryllus spp.) in food-and-feed culture systems - Edouard Bessette; Jamie Bojko; Kelly S. Bateman; Stuart Ross; Nicolai V. Meyling; Bryony A.P. Williams (Journal of Invertebrate Pathology, 2025)

Engineering Performance and Spatial Models Highlight Key Considerations for Supporting Broadscale Replacement of Environmentally Sensitive (ES) Vessel Moorings - Lincoln S. Wong; Andrew Martini; Tim P. Lynch; Carlie Devine; Lauren Hardiman; Felicity R. McEnnulty; Rick D. Stuart-Smith; D. Jeff Ross (Coastal Management, 2025)

Unifying Coral Reef States Through Space and Time Reveals a Changing Ecosystem - Simon J. Brandl; Jérémy Carlot; Rick D. Stuart‐Smith; Sally A. Keith; Nicholas A. J. Graham; Graham J. Edgar; Jérémy Wicquart; Shaun K. Wilson; Rucha Karkarey; Mary K. Donovan; Jesus E. Arias‐Gonzalez; Rohan Arthur; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological state shifts that alter the structure and function of entire ecosystems are a concerning consequence of human impact. Yet, when, where and why discrete ecological states emerge remains difficult to predict and monitor, especially in high‐diversity systems. We sought to quantify state shifts and their drivers through space and time in the most ecologically complex marine ecosystem: tropical coral reefs. Location Worldwide. Time Period 1987–2019. Major Taxa Studied Coral reef communities. Methods Using a global dataset of 3375 coral reef surveys, along with 13 time series datasets ranging between 1987 and 2019, we applied a novel double‐dichotomy approach to classify coral reefs into four simplified and discrete states based on the relative contributions of corals versus algae to benthic cover and small‐bodied versus large‐bodied fishes to fish standing stock. We then examined state shifts considering a range of spatial predictors and tested whether states have shifted directionally over time, and the nature of the most common transitions. Results We show that geographic, environmental and anthropogenic context fundamentally shapes coral reef states at the local scale, which explains disparities among case studies, and stakes out critical baseline expectations for regional management efforts. We also reveal clear multi‐decadal state shifts on coral reefs: over time, systems dominated by reef‐building corals and small‐bodied, planktivorous fishes tend to have been replaced with reefs characterised by algae and larger‐bodied fishes. Main Conclusions Our results suggest a previously unrecognised transition from systems that harness external subsidies through small‐bodied consumers associated with structurally complex live corals, to herbivore‐dominated systems with stronger bottom‐up dynamics. Overall, the partitioning of complex reef ecosystems into a small suite of discrete ecological states suggests that spatial context‐dependency, shifting baselines and changes in reef functioning are crucial considerations for coral reef management in the 21st century.

Outcrop spectral gamma-ray signals of distal arid continental basins: Facies identification and controls - Ross P. Pettigrew; Charlotte L. Priddy; Stuart M. Clarke (Marine and Petroleum Geology, 2024)

Temporal variation in the incidence of seaweed health problems affecting farmed Kappaphycus striatus in relation to environmental conditions in shallow waters - Joseph P. Faisan; Rema C. Sibonga; Jonalyn P. Mateo; Maria Rovilla J. Luhan; Victor Marco Emmanuel N. Ferriols; Vicente T. Balinas; Janina Brakel; David Bass; Stuart Ross; Grant D. Stentiford; Juliet Brodie; Georgia M. Ward; et al. (Journal of Applied Phycology, 2024)

Find the one you like! Profiling Swiss parks with user generated content - Franziska Komossa; Daniela Mariño; Annina Helena Michel; Ross Stuart Purves (Journal of Outdoor Recreation and Tourism, 2023)

Geophysical reconstruction of the late Holocene proximal proglacial landsystem at Skeiðarársandur, southeast Iceland - Devin Harrison; Neil Ross; Andrew J. Russell; Stuart J. Jones (Journal of Quaternary Science, 2023)
Sandur plains are extensive sedimentary bodies formed in proglacial settings by glaciofluvial processes. Icelandic sandar have been hypothesised to be comprised of thick alluvial successions that provide critical insight into the processes that contributed to their formation and evolution. However, to‐date, most sandar research has focused on the analysis of sedimentary successions associated to topographically‐confined and small‐scale systems. These, however, do not capture the variety or scale of processes that influence sandar architecture. Therefore, detailed subsurface analysis of large‐scale and unconfined sandar is vital to understand how these systems respond to fundamental drivers, such as: (i) glacier oscillations, and (ii) episodic sediment flux from glacier outburst floods (aka. jökulhlaups). We report an extensive, low‐frequency (40 & 100 MHz) ground‐penetrating radar (GPR) survey of the ice‐proximal component of a large‐scale () active sandur in southeast Iceland. A bright and continuous reflection (PR1) is identified within all radargrams and provides a boundary between pre‐LIA and LIA to present‐day sedimentation. GPR data reveals a ~50 m thick ice‐proximal sediment wedge that is attributed to jökulhlaup and surge‐related glaciofluvial activity during the Little Ice Age (LIA). An approximate rate of deposition of 0.2–0.65 m has been calculated for the sediment wedge above PR1. Furthermore, we propose an extensive, sandur‐wide, pre‐LIA ice marginal limit of Skeiðarárökull, southeast Iceland, based on observations reported here and in previous work.

Revising supraglacial rock avalanche magnitudes and frequencies in Glacier Bay National Park, Alaska - William D. Smith; Stuart A. Dunning; Neil Ross; Jon Telling; Erin K. Jensen; Dan H. Shugar; Jeffrey A. Coe; Marten Geertsema (Geomorphology, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Learning Together for and with the Martuwarra Fitzroy River - Rosemary Hill; Pia Harkness; Nat Raisbeck-Brown; Ilisapeci Lyons; Jorge G. Álvarez-Romero; Milena Kiatkoski Kim; Dennis Chungalla; Heather Wungundin; Mary Aiken; Jean Malay; Bernadette Williams; Rachel Buissereth; et al. (Sustainability Science, 2022)
Co-production across scientific and Indigenous knowledge systems has become a cornerstone of research to enhance knowledge, practice, ethics, and foster sustainability transformations. However, the profound differences in world views and the complex and contested histories of nation-state colonisation on Indigenous territories, highlight both opportunities and risks for Indigenous people when engaging with knowledge co-production. This paper investigates the conditions under which knowledge co-production can lead to improved Indigenous adaptive environmental planning and management among remote land-attached Indigenous peoples through a case study with ten Traditional Owner groups in the Martuwarra (Fitzroy River) Catchment in Western Australia’s Kimberley region. The research team built a 3D map of the river and used it, together with an interactive table-top projector, to bring together both scientific and Indigenous spatial knowledge. Participatory influence mapping, aligned with Traditional Owner priorities to achieve cultural governance and management planning goals set out in the Fitzroy River Declaration, investigated power relations. An analytical framework, examining underlying mechanisms of social learning, knowledge promotion and enhancing influence, based on different theories of change, was applied to unpack the immediate outcomes from these activities. The analysis identified that knowledge co-production activities improved the accessibility of the knowledge, the experiences of the knowledge users, strengthened collective identity and partnerships, and strengthened Indigenous-led institutions. The focus on cultural governance and management planning goals in the Fitzroy River Declaration enabled the activities to directly affect key drivers of Indigenous adaptive environmental planning and management—the Indigenous-led institutions. The nation-state arrangements also gave some support to local learning and decision-making through a key Indigenous institution, Martuwarra Fitzroy River Council. Knowledge co-production with remote land-attached Indigenous peoples can improve adaptive environmental planning and management where it fosters learning together, is grounded in the Indigenous-led institutions and addresses their priorities.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Joint effects of climate, tree size, and year on annual tree growth derived from tree‐ring records of ten globally distributed forests - Kristina J. Anderson‐Teixeira; Valentine Herrmann; Christine R. Rollinson; Bianca Gonzalez; Erika B. Gonzalez‐Akre; Neil Pederson; M. Ross Alexander; Craig D. Allen; Raquel Alfaro‐Sánchez; Tala Awada; Jennifer L. Baltzer; Patrick J. Baker; et al. (Global Change Biology, 2022)
Tree rings provide an invaluable long‐term record for understanding how climate and other drivers shape tree growth and forest productivity. However, conventional tree‐ring analysis methods were not designed to simultaneously test effects of climate, tree size, and other drivers on individual growth. This has limited the potential to test ecologically relevant hypotheses on tree growth sensitivity to environmental drivers and their interactions with tree size. Here, we develop and apply a new method to simultaneously model nonlinear effects of primary climate drivers, reconstructed tree diameter at breast height (DBH), and calendar year in generalized least squares models that account for the temporal autocorrelation inherent to each individual tree's growth. We analyze data from 3811 trees representing 40 species at 10 globally distributed sites, showing that precipitation, temperature, DBH, and calendar year have additively, and often interactively, influenced annual growth over the past 120 years. Growth responses were predominantly positive to precipitation (usually over ≥3‐month seasonal windows) and negative to temperature (usually maximum temperature, over ≤3‐month seasonal windows), with concave‐down responses in 63% of relationships. Climate sensitivity commonly varied with DBH (45% of cases tested), with larger trees usually more sensitive. Trends in ring width at small DBH were linked to the light environment under which trees established, but basal area or biomass increments consistently reached maxima at intermediate DBH. Accounting for climate and DBH, growth rate declined over time for 92% of species in secondary or disturbed stands, whereas growth trends were mixed in older forests. These trends were largely attributable to stand dynamics as cohorts and stands age, which remain challenging to disentangle from global change drivers. By providing a parsimonious approach for characterizing multiple interacting drivers of tree growth, our method reveals a more complete picture of the factors influencing growth than has previously been possible.

Preliminary survey of pests and diseases of eucheumatoid seaweed farms in the Philippines - Joseph P. Faisan; Ma. Rovilla J. Luhan; Rema C. Sibonga; Jonalyn P. Mateo; Victor Marco Emmanuel N. Ferriols; Janina Brakel; Georgia M. Ward; Stuart Ross; David Bass; Grant D. Stentiford; Juliet Brodie; Anicia Q. Hurtado (Journal of Applied Phycology, 2021)

Nucleus incertus promotes cortical desynchronization and behavioral arousal - Sherie Ma; Giancarlo Allocca; Emma K. E. Ong-Pålsson; Caitlin E. Singleton; David Hawkes; Stuart J. McDougall; Spencer J. Williams; Ross A. D. Bathgate; Andrew L. Gundlach (Brain Structure and Function, 2017)

Using CBPR to Extend Prostate Cancer Education, Counseling, and Screening Opportunities to Urban-Dwelling African-Americans - Levi Ross; Jarrett Johnson; Stacy W. Smallwood; John S. Luque; Stuart H. Tedders; Collins O. Airhihenbuwa; Terry Alford; Willie Underwood (Journal of Cancer Education, 2016)

Ecological and socio-economic factors affecting extinction risk in parrots - George Olah; Stuart H. M. Butchart; Andy Symes; Iliana Medina Guzmán; Ross Cunningham; Donald J. Brightsmith; Robert Heinsohn (Biodiversity and Conservation, 2016)

Understanding Human–Coyote Encounters in Urban Ecosystems Using Citizen Science Data: What Do Socioeconomics Tell Us? - Stuart Wine; Sara A. Gagné; Ross K. Meentemeyer (Environmental Management, 2015)

A reconstruction of extratropical Indo-Pacific sea-level pressure patterns during the Medieval Climate Anomaly - Ian D. Goodwin; Stuart Browning; Andrew M. Lorrey; Paul A. Mayewski; Steven J. Phipps; Nancy A. N. Bertler; Ross P. Edwards; Tim J. Cohen; Tas van Ommen; Mark Curran; Cameron Barr; J. Curt Stager (Climate Dynamics, 2014)

Challenges in understanding the sources of bioaccumulated metals in biota inhabiting turbid river systems - Tom Cresswell; Ross E. W. Smith; Stuart L. Simpson (Environmental Science and Pollution Research, 2014)

Challenges with tracing the fate and speciation of mine-derived metals in turbid river systems: implications for bioavailability - Tom Cresswell; Ross E. W. Smith; Dayanthi Nugegoda; Stuart L. Simpson (Environmental Science and Pollution Research, 2013)

Bovine Muc1 inhibits binding of enteric bacteria to Caco-2 cells - Phillip Parker; Lillian Sando; Roger Pearson; Kritaya Kongsuwan; Ross L. Tellam; Stuart Smith (Glycoconjugate Journal, 2010)

Possible impacts of anthropogenic and natural aerosols on Australian climate: a review - Leon D. Rotstayn; Melita D. Keywood; Bruce W. Forgan; Albert J. Gabric; Ian E. Galbally; John L. Gras; Ashok K. Luhar; Grant H. McTainsh; Ross M. Mitchell; Stuart A. Young (International Journal of Climatology, 2009)
A review is presented of the aerosol–climate interaction with specific focus on the Australian region. The uncertainties associated with this interaction are much larger than those associated with greenhouse gases or other forcing agents, and are currently a major obstacle in climate‐change research. However, new research suggests that aerosol effects are of comparable importance to greenhouse gases as a driver of recent climate trends in the Southern Hemisphere, including Australia. A significant new result from climate modelling is that anthropogenic aerosol over Asia affects meridional temperature gradients and atmospheric circulation, and may have caused an increase in rainfall over north‐western Australia. Global ocean circulation provides another mechanism whereby aerosol changes in the Northern Hemisphere can affect climate in the Southern Hemisphere, suggesting an urgent need for further targeted studies using coupled ocean‐atmosphere global climate models. To better model climate variability and climate change in the Australian region, more research is needed into the sources of aerosol and their precursors, their atmospheric distributions and transformations, and how to incorporate these processes robustly in global climate models (GCMs). The following priorities are suggested for further research in Australia linking aerosol observations and modelling: natural aerosol over the Southern Ocean, tropical biomass‐burning aerosol in Indonesia and Australia, secondary organic aerosol (SOA) from volatile organic compounds (VOCs), wind‐blown dust and modulation of rainfall by anthropogenic aerosol. Copyright © 2008 Royal Meteorological Society

The timing of ovulation with respect to sexual swelling detumescence in wild olive baboons - James P. Higham; Michael Heistermann; Caroline Ross; Stuart Semple; Ann MacLarnon (Primates, 2008)

Gastrointestinal Parasites in Crop Raiding and Wild Foraging Papio anubis in Nigeria - Anna H. Weyher; Caroline Ross; Stuart Semple (International Journal of Primatology, 2006)

Interaction of hydrology and nutrient limitation in the Ridge and Slough landscape of the southern Everglades - Michael S. Ross; Sherry Mitchell-Bruker; Jay P. Sah; Stuart Stothoff; Pablo L. Ruiz; David L. Reed; Kris Jayachandran; Charles L. Coultas (Hydrobiologia, 2006)

The human FK506-binding proteins: characterization of human FKBP19 - Stuart L. Rulten; Ross A. Kinloch; Hilda Tateossian; Colin Robinson; Lucy Gettins; John E. Kay (Mammalian Genome, 2006)

A continental scale evaluation of the role of limpet grazing on rocky shores - Ross A. Coleman; Antony J. Underwood; Lisandro Benedetti-Cecchi; Per Åberg; Francisco Arenas; Julio Arrontes; João Castro; Richard G. Hartnoll; Stuart R. Jenkins; José Paula; Paolo Della Santina; Stephen J. Hawkins (Oecologia, 2006)

Lunar science: An overview - Stuart Ross Taylor (Journal of Earth System Science, 2005)

Distribution and diversity of soil protozoa in the McMurdo Dry Valleys of Antarctica - Stuart S. Bamforth; Diana H. Wall; Ross A. Virginia (Polar Biology, 2005)

Lewis Ponds, a hybrid carbonate and volcanic-hosted polymetallic massive sulphide deposit, New South Wales, Australia - Michael W. Agnew; Ross R. Large; Stuart W. Bull (Mineralium Deposita, 2005)

Numerical investigation of salinity in controlling ore-forming fluid transport in sedimentary basins: example of the HYC deposit, Northern Australia - Jianwen Yang; Stuart Bull; Ross Large (Mineralium Deposita, 2004)

Mass flow sedimentology within the HYC Zn?Pb?Ag deposit, Northern Territory, Australia: evidence for syn-sedimentary ore genesis - Tim Ireland; Stuart W. Bull; Ross R. Large (Mineralium Deposita, 2004)

Limit dextrinase from germinating barley has endotransglycosylase activity, which explains its activation by maltodextrins - Gordon J. McDougall; Heather A. Ross; J. Stuart Swanston; Howard V. Davies (Planta, 2004)

Using LCA to examine greenhouse gas abatement policy - Stuart Ross; David Evans; Michael Webber (The International Journal of Life Cycle Assessment, 2003)

The use of life cycle assessment in environmental management - Stuart Ross; David Evans (The International Journal of Life Cycle Assessment, 2002)

Excluding site-specific data from the lca inventory: how this affects life cycle impact assessment - Stuart Ross; David Evans (The International Journal of Life Cycle Assessment, 2002)

How LCA studies deal with uncertainty - Stuart Ross; David Evans; Michael Webber (The International Journal of Life Cycle Assessment, 2002)

Use of Life Cycle Assessment in Environmental Management - Stuart Ross; David Evans (Environmental Management, 2002)